2022
DOI: 10.3389/fcimb.2022.944611
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin affects function of Hsp90 and drug efflux pump of Candida albicans

Abstract: Candida albicans is a pathogenic yeast that causes candidiasis in immunocompromised patients. The overuse of antifungal drugs has led to the development of resistance to such drugs by this fungus, which is a major challenge in antifungal chemotherapy. One approach to this problem involves the utilization of new natural products as an alternative source of antifungals. Curcumin, one such natural product, has been widely studied as a drug candidate and is reported to exhibit antifungal activity against C. albica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 92 publications
3
5
0
Order By: Relevance
“…The clinical relevance of MCZ has also been shown to be better than other drugs of its class, such as clotrimazole, which has a lower cure rate and a higher risk of relapse [ 53 , 54 ]. The therapeutic efficacy of MCZ can also be enhanced by synergism with CUR, which acts by complementary mechanisms such as inhibiting hyphal development, altering membrane permeability, and inhibiting biofilms [ 55 ]. Therefore, CUR and MCZ combined in a modified-release formulation based on U-PEO can contribute positively to improving the clinical response to the treatment of VVC.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical relevance of MCZ has also been shown to be better than other drugs of its class, such as clotrimazole, which has a lower cure rate and a higher risk of relapse [ 53 , 54 ]. The therapeutic efficacy of MCZ can also be enhanced by synergism with CUR, which acts by complementary mechanisms such as inhibiting hyphal development, altering membrane permeability, and inhibiting biofilms [ 55 ]. Therefore, CUR and MCZ combined in a modified-release formulation based on U-PEO can contribute positively to improving the clinical response to the treatment of VVC.…”
Section: Resultsmentioning
confidence: 99%
“…[258][259][260] Curcumin, a polyphenol first isolated from the root of herbaceous Curcuma longa in 1815, is well-known for its potent antitumor and anti-inflammatory activity. 261 Jung et al 262 observed that curcumin induces the degradation of ErbB2 and Lee et al 263 showed that curcumin increases degradation of HSP90 mRNA. The efficacy of curcumin in treating head and neck neoplasms has been investigated through successful phase II clinical trials (No: NCT04208334 and NCT01160302), demonstrating that curcumin treatment is safe and well-tolerated.…”
Section: Ppi Compoundsmentioning
confidence: 99%
“…Jung et al 262 . observed that curcumin induces the degradation of ErbB2 and Lee et al 263 . showed that curcumin increases degradation of HSP90 mRNA.…”
Section: Hsp90 Inhibitors For Cancer Treatmentmentioning
confidence: 99%
“…This compound has been reported for the treatment of diseases of the oral site, such as OPC and Candida -related denture stomatitis [102]. Lee et al [46] assessed the role of curcumin in C. albicans treatment using a doxycycline-mediated heat shock protein 90 (HSP90) strain and an HSP90-overexpressing strain of C. albicans . They demonstrated that curcumin can lead to the downregulation of CDR1 and the inhibition of efflux pump activity of CDR1.…”
Section: Natural Compounds With Anti-candida Activitiesmentioning
confidence: 99%
“…They demonstrated that curcumin can lead to the downregulation of CDR1 and the inhibition of efflux pump activity of CDR1. So, curcumin could impair cell growth, stress responses, and efflux pump activity of C. albicans ( p < 0.05) [46] (Table 2). Lichochalcone-A is another natural polyphenol with protective activities, especially antimicrobials and anti-biofilm formation [50].…”
Section: Natural Compounds With Anti-candida Activitiesmentioning
confidence: 99%